Effects of the Conditional Cash Transfer Program on the Socio-Economic Conditions of Beneficiaries - Pancho, Mary Vir; Ballados, Ma. Teresa (Journal of Interdisciplinary Perspectives, 2025)
This study investigated the effects of the Conditional Cash Transfer (CCT) program on the social and economic conditions of household beneficiaries in Kabankalan, Negros Occidental. It focused on key areas such as education, health, nutrition, women's empowerment, household consumption, income, investment, and savings. A descriptive-correlational research design was utilized, with data gathered through a researcher-made questionnaire distributed to 383 women grantees from registered, clean, and active households as of January 10, 2025. Participants were selected using stratified random sampling and were categorized into lowland and upland barangays. The results indicated that the extent of the CCT program's effects on household beneficiaries’ social conditions, particularly regarding education, health, nutrition, and women's empowerment, was very great. These effects were evident across different household sizes, locations, and how many years beneficiaries had participated in the program. Additionally, the program had a pronounced impact on the economic conditions of the beneficiaries, specifically concerning household consumption, income, investment, and savings. A significant difference was observed in the extent of the effects of the CCT program on the social conditions of household beneficiaries when grouped by location. Location emerged as a predictor of economic outcomes. In conclusion, the CCT program significantly enhances beneficiaries' social and financial well-being, though its effectiveness varies by location. Future enhancements to the program should incorporate additional support services tailored to the unique needs of different households to maximize the effects of the CCT program.